Quasi-static compression behavior of nickel oxide, nickel oxide:zirconia, nickel:zirconia and nickel foams. Issue 9 (July 2016) - Biswas, Papiya; Ramavath, Pandu; Nair, Chandhana Muraleedharan; Buchi Suresh, Madireddy; Ravi, Nakula; Johnson, Roy
Abstract: An effective material for use in shock mitigation should spread the deflection of the shock wave over a longer period of time and should minimize the force felt by the object under impact. Ductile or brittle cellular materials are currently gaining importance due to their unique high energy absorption characteristics. Reticulated cellular foam structures of nickel oxide (NiO) and nickel oxide:zirconia (NiO:YSZ 60:40 percentage by wt.) were fabricated by polymeric sponge replication process. These foams are reduced under hydrogen atmosphere to produce metallic nickel (Ni) and nickel:zirconia (Ni:YSZ) cermet foams, respectively. X-ray diffraction studies on the struts confirmed the corresponding phase formation. Further, the volume fraction of the solid in foam is estimated through image analysis. All the foams are subjected to uni-axial compression and the stress–strain curves were recorded. A comparative evaluation of progressive deformation behavior at room temperature was also carried out. Stress–strain curve of the nickel foam shows distinctly three regimes under compression, a deformation regime showing a linear dependence in the strain with stress. This is followed by a second region showing a plateau corresponding to the energy absorption resulting from the permanent plastic deformation while retaining the integrity and finally densification region through the wall collapse resulting in the maximum compressive strength. Stress–strain curves of all other foams such as NiO, NiO:YSZ and Ni:YSZ has demonstrated a similar fracture behavior under compression which caused not only by unstable crack propagation originating from a single crack, but also by merging of many cracks leading to the formation of the crushed zone. Compressive strength is found to be a strong function of solid fraction supporting the load and percentage porosity of NiO foams. Estimation of relative energy absorption has exhibited higher energy absorption irrespective of the material of construction at higher strain rates.